SIIM Announces New Awards! - Krupinski, Elizabeth A. (Journal of Digital Imaging, 2020)
The Society for Imaging Informatics in Medicine (SIIM) has created six new awards to be inaugurated at the 2020 Annual Meeting. These include the Gold Medal of the Society, The Joe Gitlin Award, the Dr. Ruth Dayhoff Award for the Advancement of Women in Medical Imaging Informatics, the Imaging Informatics Innovator Award, the Early Career Achievement Award, and the Educator Award. The award criteria, nomination, and selection processes are outlined in this paper with the goal of encouraging nominations (including self-nominations) for these prestigious awards recognizing contributions to imaging informatics in medicine.